A New Triangular Muscle Flap Esophagogastrostomy After Proximal Gastrectomy - Guangyu Chen; Zhenyu Chen; Yaning Song; Baifa Sheng; Xiong Li; Lin Zhang; Yongkuan Cao; Lin Xue; Liye Liu (Journal of Investigative Surgery)
Background Standardized proximal gastrectomy for upper-third gastric cancer (UGC) is lacking due to the current methods’ inability to prevent reflux and facilitate postoperative endoscopic monitoring surveillance. In this study, we provide a detailed description of proximal gastrectomy utilizing a new triangular muscle flap for esophagogastrostomy and evaluate the postoperative outcomes of this technique.Method A total of 17 patients diagnosed with early-stage primary UGC underwent laparoscopic proximal gastrectomy between May 2021 and May 2022. Subsequently, a new triangular muscle flap was used for esophagogastrostomy.Results No in-hospital deaths occurred during the study period. However, two patients experienced complications early in the study, including one case of pulmonary infection and another of abdominal abscess infection. Importantly, none of the patients exhibited any reflux symptoms. Postoperatively, 15 patients were diagnosed with grade N/M esophagitis, one with grade A, and one with grade B. All patients are currently alive without tumor recurrence.Conclusions This surgical technique can be safely performed and demonstrates excellent results in preventing gastroesophageal reflux. Further investigation through a multi-center clinical study is warranted to confirm its efficacy.